Validation of International Reference Ionosphere model (IRI-2016) for F-region peak electron density height (hmF2): Comparison with Incoherent Scatter Radar (ISR) and ionosonde measurements at Millstone Hill. Issue 12 (15th June 2020) - Mengist, C.K.; Yadav, S.; Kotulak, K.; Bahar, A.; Zhang, S.-R.; Seo, K.-H.
Abstract: In this report, we have evaluated the performance of International Reference Ionosphere (IRI-2016) model in predicting the diurnal variation of F-region peak electron density height (hmF2) at Millstone Hill (MH, 42.6°N, 288.5°E) during the solar cycle 24 for both high and low-solar activity years. The new methodology is adopted to derive hmF2 values from the Incoherent Scatter Radar (ISR) measurements. The hmF2 derived from ISR along with ionosonde measurements operating at MH has been used to evaluate the performance of IRI-2016 model. The IRI-2016 model has three options to predict hmF2, namely, BSE-1979, AMTB-2013, and SHU-2015. The observed hmF2 from ISR and ionosonde are compared with all the three options provided by IRI-2016 to predict hmF2. Results show that hmF2 from IRI-2016, ISR and ionosonde exhibit similar diurnal variation. The deviations between measurements and model predictions were found to increase during nighttime. The SHU-2015 model emerged out to be the best in predicting the hmF2 values over MH as compared to other two options. The BSE-1979 option also provides reasonably better prediction as compared to the relatively latest AMTB-2013 options. Based on this statistical analyses, we recommend SHU-2015 option of IRI-2016 hmF2 model over MH area.